2020
DOI: 10.32598/rj.21.1.2874.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Competence Training on Tendency Towards High-Risk Behaviors in Male Adolescents Living in Welfare Boarding Centers

Abstract: Objective High-risk behaviors are seriously threatening health and wellbeing, and increasing the likelihood of physical, psychological, and social consequences. High-risk behaviors, such as tobacco use, drug abuse, alcohol use, or malicious behaviors can endanger the health and wellbeing of adolescents and hinder their success and future growth. Today, the prevalence of high-risk behaviors among adolescents has become one of the most important concerns in society and despite the provisions made in recent years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Every year, 10 thousand teenagers in the United States die due to completely preventable reasons such as not observing safe behaviors (6). Studies have demonstrated that most traffic accidents result from people's unsafe behaviors (7) Alizadeh et al reported that the prevalence of high-risk behaviors among Iranian teenagers is high, and it is essential to address the issue of high-risk behaviors Theory-based training in promoting safe traffic behaviors because they induce personal and social problems and deaths from accidents (8). Based on the studies conducted and the statistics of the Forensic Medicine Organization of Iran, about 30% of the pedestrians killed in traffic accidents at school age (less than 18 years old) are trapped.…”
Section: Introductionmentioning
confidence: 99%
“…Every year, 10 thousand teenagers in the United States die due to completely preventable reasons such as not observing safe behaviors (6). Studies have demonstrated that most traffic accidents result from people's unsafe behaviors (7) Alizadeh et al reported that the prevalence of high-risk behaviors among Iranian teenagers is high, and it is essential to address the issue of high-risk behaviors Theory-based training in promoting safe traffic behaviors because they induce personal and social problems and deaths from accidents (8). Based on the studies conducted and the statistics of the Forensic Medicine Organization of Iran, about 30% of the pedestrians killed in traffic accidents at school age (less than 18 years old) are trapped.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2016 census, about six million people in Iran were 14-19 years old, which was approximately equivalent to seven percent of the total population of the country. Due to the young population of Iran and the unpreparedness of adolescents in terms of tools needed to deal with the issues or characteristics of adolescence that in many cases contribute to dangerous and troublesome behaviors and tasks, the issue of social and mental health of adolescents as at-risk groups is one of the main priorities of the country (Alizadeh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%